Feline immunodeficiency virus infection - Medeiros, Sheila de Oliveira; Pierucci, Julia [UNESP] (My University, 2015)
Feline Immunodeficiency Virus (FIV) is one of most common feline viral diseases, affecting wild and domestic cats worldwide. FIV belongs to the Retroviridae family, the most famous representative of which is Human Immunodeficiency Virus (HIV). The main mode of transmission is through bite wounds, but vertical transmission is also possible. Based on the mode of transmission, unneutered male outdoor cats are the highest-risk group. The infection is characterized by a long incubation period and a persistent infection, with development of acquired immune deficiency syndrome (AIDS), similar to HIV. In this stage the cat is susceptible to secondary and opportunistic infections. Infected cats may develop different clinical conditions, such as tumors and renal disease, but one of the most common manifestations is oral cavity disease. An FIV vaccine is available, but identification and isolation of infected cats is recommended as a preventive measure. FIV was isolated in 1986 in a colony of cats with opportunistic infections. Since then, relatively little research has been done on some aspects of the infection, like chronic or terminal stages of the disease, and mainly with respect to antiviral treatment. The purpose of this chapter is to update, through literature review, some aspects of clinical, epidemiological, diagnostics and treatments of FIV infection in the domestic cat.